Tourists as storytellers of tourist destinations, case study of Rammang-Rammang Karst - Mukarramah Machmud; Muhammad Hasyim (Universitas Merdeka Malang, 2022)
Storytelling represents a story about a tourist destination. Travelers have stories about objects, and they become the Storyteller of the objects visited. This article aims to explore the use of travelers to the objects visited and how their knowledge becomes storytelling. The tourist destination that is object of study is the karst tourist destination Rammang-Rammang, a place in the Karst mountain cluster Maros-Pangkep Indonesia. This paper will use narration theory as a communication system for creating stories against an object. The results of this study showed that elements are forming the stories Rammang-Rammang as the attraction of ecotourism, namely living culture Rammang-Rammang, mangrove trees, Nipah palm, rivers, boats, karst, caves, Empang and house Traditional Bugis. Tourists can tell stories (myths) from the elements of the stories. Tourists as storytellers against Rammang-Rammang Ecotourism as a media promotion of tourism. Tourists, as the storyteller promotes objects visited.